Walk through fire - Johnson, Sheila, 1949-; Dickey, Lisa (Simon & Schuster, 2023)
"The cofounder of BET and first African American woman billionaire shares her deeply personal journey through love and loss, tragedy and triumph--an inspiring story of overcoming toxic influences, discovering her true self, and at last finding happiness in her work and life. From humble beginnings as a schoolgirl and young violinist in Maywood, Illinois, Sheila Johnson rose to become one of the most accomplished businesswomen in America. A cofounder of Black Entertainment Television, she became an entrepreneur and philanthropist at the highest levels. But that success came at a painful personal cost. Sheila grew up in a middle-class family that encouraged her love of the arts and music. But her idyllic childhood ended at age sixteen when her beloved father announced he was leaving for another woman, an act that shattered her mother and destroyed Sheila's trust. She vowed she'd never be in her mother's position--dependent on a man for her sense of self-worth and for financial security. Yet when she was barely out of her teens, Sheila married a man who would take her right down that same unfortunate path. Filled with sharply drawn, emotionally powerful scenes, Walk Through Fire traces the hardships Sheila faced in her marriage and her professional life. Despite her skills as a violinist and music teacher, as well as her obvious entrepreneurial talent, she had to fight to overcome self-doubt and fears of failure. Sheila vividly details her struggles, including battling institutional racism, losing a child, suffering emotional abuse in her thirty-three-year marriage, and plunging into a deep depression with her divorce. And yet, out of that pain came renewed purpose and meaning. In the third act of her life, Sheila Johnson has not only made her mark as the founder of Salamander Hotels & Resorts and the only Black female co-owner of three professional sports teams, she has also, finally, found true love. Walk through fire is a uniquely American success story. And it is the deeply personal portrait of one woman who, despite heartache and obstacles, finally found herself and her place in the world" --